Novel Agmatine Derivatives in Maerua edulis With Bioactivity Against Callosobruchus maculatus, a Cosmopolitan Storage Insect Pest - Stevenson, Philip C.; Green, Paul W. C.; Farrell, Iain W.; Brankin, Alice; Mvumi, Brighton M.; Belmain, Steven R. (Frontiers in Plant Science, 2018)
Agricultural intensification in smallholder farming is crucial to feeding Africa and supporting global nutritional security since these farmers produce 80% of the food in the developing world. However, these farming systems are low input and so are particularly vulnerable to crop losses due to insects, particularly in storage where up to 40% losses are common. Synthetic pesticides can vary in their effectiveness but may be unavailable or adulterated. Pesticides also persist in the environment affecting beneficial arthropods and can be poisonous to farmers and consumers, so alternatives are required. Plant materials have been part of the farmer’s armoury against pests for generations and are still a relevant alternative to synthetics as they are readily available and are typically less toxic to humans and beneficial insects. Blue bush-berry, Maerua edulis, is a shrub native to Southern Africa. Recent work reported pest control efficacy of this species against cattle ticks and storage beetles, but little is known about the chemistry underlying the activity. Chemical information is essential to understanding the nature of and variations in activity from different locations and helping to develop ways of optimising use for farmers. Here we report the identification of cinnamoyl and 4-hydroxycinnamoyl amides of agmatine ((4-aminobutyl) guanidine) that occur in the leaves of M. edulis. Their structures were elucidated by various spectroscopic techniques. Stachydrine and 3-hydroxystachydrine were also identified in the leaves at high concentrations. We tested these compounds against the major storage pests of legumes, the cowpea bruchid Callosobruchus maculatus, and show that these compounds are biologically active against this pest and may account for the activity reported in this plant to other pest arthropods. We also report a synthesis of the amides which could help produce adequate quantities for testing against other pests and may even lead to a commercial synthesis.